Liverworts of the South Kamchatka Nature Park: Survival in active volcanism land - Bakalin, Vadim A.; Klimova, Ksenia G.; Karpov, Eugeniy A.; Bakalin, Daniil A.; Choi, Seung Se (Diversity)
Tetralophozia filiformis s.l. is known from a number of localities mostly in amphi-oceanic areas in Northern Hemisphere, including Atlantic Europe, amphi-Pacific Asia, South Siberia, and western North America. The newly obtained collections of this 'species' show strong variation in morphology of the taxon across amphi-Pacific Asia although connected by some 'intergrading' modifications. This implies the genetic diversity within this unit earlier recognized as a single taxon. Authors used molecular-genetic, morphological, and chorological methods to understand if the geographically correlated morphological variation also correlates with genetic differences and if it is possible to distinguish some additional taxa within the series of specimens originating from the various areas in amphi-Pacific Asia. It was found that Tetralophozia filiformis is a complex of at least three morphologically similar species, including one long forgotten name (Chandonanthus pusillus) that should be reinstated as separate species and one taxon (Tetralophozia sibirica) that should be described as new. Tetralophozia filiformis and Chandonanthus pusillus are lectotypified, and the new combination is provided for the latter. The three accepted taxa distinctly differ one from another in distribution patterns, preferable climate characteristics, and genetic distances, besides minor differentiations in morphology. The main morphological distinguishing features are the leaf cell size, height of undivided part in leaf lamina, and leaf dentation characteristics. Taking into account the robust correlation between the climate-based and molecular-genetic-based clusters, one more (fourth) taxon could be probably segregated from Tetralophozia filiformis.